7
$\begingroup$

How do we find $$S=\sum_{k=1}^{\infty} \left[\frac{1}{2k} -\log\left(1+\dfrac{1}{2k}\right)\right]$$

I know that $\displaystyle\sum_{k=1}^{\infty} \left[\frac{1}{k} -\log\left(1+\dfrac{1}{k}\right)\right]=\gamma$, where $\gamma$ is the Euler–Mascheroni constant.

But I could not manipulate this series.

$\endgroup$
  • 1
    $\begingroup$ @graydad The log sum telescopes. $\endgroup$ – Pedro Tamaroff Oct 5 '14 at 15:52
19
$\begingroup$

Start with the infinite product expansion of Gamma function,

$$\frac{1}{\Gamma(z)} = z e^{\gamma z}\prod_{k=1}^\infty \left(1 + \frac{z}{k}\right) e^{-\frac{z}{k}}$$

Taking logarithm and rearrange terms, one get

$$\begin{align} & -\log\Gamma(z) = \log z + \gamma z + \sum_{k=1}^\infty \left[\log\left(1+\frac{z}{k}\right) - \frac{z}{k}\right]\\ \implies & \sum_{k=1}^\infty \left[\frac{z}{k} - \log\left(1+\frac{z}{k}\right) \right] = \log z + \gamma z + \log\Gamma(z) \end{align}$$ Taking $z = \frac12$ and use the known value of $\Gamma\left(\frac12\right) = \sqrt{\pi}$, we get

$$\sum_{k=1}^\infty \left[\frac{1}{2k} - \log\left(1+\frac{1}{2k}\right) \right] = \frac12\left(\gamma + \log\pi\right) - \log 2 $$

$\endgroup$
7
$\begingroup$

Observe that, by absolute convergence: $$\begin{align} \sum_{k=1}^{\infty} \left(\frac{1}{2k} -\log\left(1+\dfrac{1}{2k}\right)\right)& =\sum_{k=1}^{\infty} \dfrac{1+(-1)^k}{2}\left(\frac{1}{k} -\log\left(1+\dfrac{1}{k}\right)\right)\\\\ &=\frac{1}{2}\sum_{k=1}^{\infty} \!\left(\frac{1}{k} -\log\left(1+\dfrac{1}{k}\!\right)\right)\!+\!\frac{1}{2}\!\sum_{k=1}^{\infty} (-1)^{k-1}\left(\!\frac{1}{k} -\log\!\left(1+\dfrac{1}{k}\!\right)\!\right) \\\\ &=\frac{\gamma}{2}+\!\frac{1}{2}\!\sum_{k=1}^{\infty} (-1)^{k-1}\left(\!\frac{1}{k} -\log\!\left(1+\dfrac{1}{k}\!\right)\!\right). \end{align} $$ Then, as $N$ is great, write $$ \begin{align} \sum_{k=1}^{N} (-1)^{k-1}\left(\!\frac{1}{k} -\log\!\left(1+\dfrac{1}{k}\!\right)\!\right)& =\sum_{k=1}^{N}(-1)^{k-1} \frac{1}{k}-\sum_{k=1}^{N} (-1)^{k-1}\log\!\left(1+\dfrac{1}{k}\!\right)\\\\ &=\sum_{k=1}^{N}(-1)^{k-1} \frac{1}{k}-\log \left(\prod_{k=1}^{N} \left(1+\dfrac{1}{k}\!\right)^{(-1)^{k-1}}\right) \tag2 \end{align} $$ giving $$ \begin{align} \sum_{k=1}^{\infty} (-1)^{k-1}\left(\!\frac{1}{k} -\log\!\left(1+\dfrac{1}{k}\!\right)\!\right)=\log 2-\log \left(\frac{\pi}{2}\right) \end{align} $$ where we have used Wallis' product formula for $\pi$.

Finally we obtain

$$ \sum_{k=1}^{\infty} \left(\frac{1}{2k} -\log\left(1+\dfrac{1}{2k}\right)\right)=\frac{\gamma}{2}-\frac{1}{2}\log \left(\frac{4}{\pi}\right). $$

$\endgroup$
3
$\begingroup$

Consider the series \begin{align} S = \sum_{k=1}^{\infty} \left[ \frac{1}{2k} - \ln\left(1 + \frac{1}{2k}\right) \right] \end{align} for which, by using the logarithm in series form, it becomes \begin{align} S &= \sum_{k=1}^{\infty} \left[ \frac{1}{2k} - \frac{1}{2k} + \sum_{n=2}^{\infty} \frac{(-1)^{n}}{n \, (2k)^{n}} \right] \\ &= \sum_{k=1}^{\infty} \sum_{n=2}^{\infty} \frac{(-1/2)^{n}}{n \, k^{n}} \\ &= \sum_{n=2}^{\infty} \frac{(-1/2)^{n}}{n} \, \zeta(n) \\ &= \sum_{n=1}^{\infty} \frac{(-1/2)^{n+1}}{n+1} \, \zeta(n+1). \end{align} Now the generating function for the zeta function is given by \begin{align} \sum_{n=1}^{\infty} \zeta(n+1) (-1)^{n+1} x^{n} = \gamma + \psi(x+1) \end{align} and by integration leads to \begin{align} \sum_{n=1}^{\infty} \frac{(-x)^{n+1}}{n+1} \, \zeta(n+1) = \gamma x + \ln\Gamma(x+1). \end{align} Letting $x = 1/2$ in this series leads to the value of the series for $S$, namely \begin{align} \sum_{k=1}^{\infty} \left[ \frac{1}{2k} - \ln\left(1 + \frac{1}{2k}\right) \right] = \frac{1}{2} \ln\left(\frac{\pi}{4}\right) + \frac{\gamma}{2}. \end{align}

$\endgroup$
2
$\begingroup$

If I have well understood, you want the limit of $\displaystyle S_n=\sum_{k=1}^n (\frac{1}{2k}-\log(1+\frac{1}{2k}))$.

We have $$\sum_{k=1}^n \frac{1}{k}=\log(n+1)+\gamma+\varepsilon_n$$ with $\varepsilon_n\to 0$ as $n\to +\infty$. Now: $$S_n=\frac{1}{2}(\sum_{k=1}^n\frac{1}{k})-\sum_{k=1}^n \log(2k+1)+\sum_{k=1}^n \log(2k)=\frac{1}{2}(\sum_{k=1}^n\frac{1}{k})-\sum_{k=1}^n (\log(2k+1)+\log(2k))+2\sum_{k=1}^n \log(2k)$$ Hence: $$S_n=\frac{\gamma}{2}+\frac{1}{2}\log(n+1)+\frac{\varepsilon_n}{2}-\log(2n+1)!+2n\log 2+2\log n!$$

Thus: $$S_n=\frac{\gamma}{2}+\frac{\varepsilon_n}{2}+\log A_n$$ With $\displaystyle A_n=\frac{2^{2n}(n!)^2\sqrt{n+1}}{(2n+1)!}$. Now use Stirling's Formula to finish.

$\endgroup$
1
$\begingroup$

You can do it by calulating the n-th partial sum and taking the limit:

Let $S_n=\sum_{k=1}^{n} \left[\frac{1}{2k} -\log\left(1+\dfrac{1}{2k}\right)\right]$. Then:

$$ S_n=\frac{1}{2}H_n -\log\left(\prod_{k=1}^n\dfrac{2k+1}{2k}\right)=\frac{1}{2}H_n -\log\left(\dfrac{(2n+1)!!}{(2n)!!}\right)=\frac{1}{2}H_n -\log\left(\dfrac{(2n+1)!}{2^{2n}(n!)^2}\right) $$

By Stirlings approximation, we have

$$ n!=\sqrt{2\pi}\cdot n^{n+\frac{1}{2}}\cdot e^{-n}\cdot e^{\frac{\theta_n}{12n}} $$

With $0\lt\theta_n\lt1$. Making this substitution in the fomula above, we get:

$$ S_n=\frac{1}{2}H_n -\log\left(\dfrac{\sqrt{2\pi}\cdot(2n+1)^{2n+1+\frac{1}{2}}\cdot e^{-2n-1}\cdot e^{\frac{\theta_{2n+1}}{12(2n+1)}}}{2^{2n}\cdot 2\pi\cdot n^{2n+1} \cdot e^{-2n}\cdot e^{\frac{\theta_n}{6n}}}\right)=\frac{1}{2}H_n -\log\left(\dfrac{2\cdot(1+\frac{1}{2n})^{2n+1}\cdot \sqrt{n+\frac{1}{2}}\cdot e^{\frac{\theta_{2n+1}}{12(2n+1)}}}{\sqrt{\pi}\cdot e\cdot e^{\frac{\theta_n}{6n}}}\right)=\frac{1}{2}H_n -\frac{1}{2}\log\left(n+\frac{1}{2}\right)-\log\left(\dfrac{2\cdot(1+\frac{1}{2n})^{2n+1}\cdot e^{\frac{\theta_{2n+1}}{12(2n+1)}}}{\sqrt{\pi}\cdot e\cdot e^{\frac{\theta_n}{6n}}}\right) $$

So by taking the limit, we get:

$$ S=\lim_{n \to \infty}S_n=\lim_{n \to \infty}{\left[\frac{1}{2}H_n -\frac{1}{2}\log\left(n+\frac{1}{2}\right)-\log\left(\dfrac{2\cdot(1+\frac{1}{2n})^{2n+1}\cdot e^{\frac{\theta_{2n+1}}{12(2n+1)}}}{\sqrt{\pi}\cdot e\cdot e^{\frac{\theta_n}{6n}}}\right)\right]=\frac{\gamma}{2}-\log(2)+\frac{1}{2}\log{(\pi)}} $$

Which seems to be true since Wolfram alpha gives:

$$ \sum_{k=1}^{\infty} \left[\frac{1}{2k} -\log\left(1+\dfrac{1}{2k}\right)\right] \approx 0.1678255948155212079577375992595540032692269400673623 $$

While:

$$ \frac{\gamma}{2}-\log(2)+\frac{1}{2}\log{(\pi)} \approx 0.1678255948155212079577375992595540032692269400673623 $$

$\endgroup$
1
$\begingroup$

Notice that $$S=\sum^{\infty}_{k=1}\Big(\frac{1}{2k}-\frac{1}{2}\log(1+\frac{1}{k})+\frac{1}{2}\log(1+\frac{1}{k})-\frac{2}{2}\log(1+\frac{1}{2k})\Big)$$ Therefore $$S=\frac{1}{2}\gamma+\frac{1}{2}\sum^{\infty}_{k=1}\log\Big(\frac{1+\frac{1}{k}}{(1+\frac{1}{2k})^2}\Big)$$ In other words \begin{align} S=\frac{1}{2}\gamma+\frac{1}{2}\log\Big(\prod^{\infty}_{k=1}\frac{1+\frac{1}{k}}{(1+\frac{1}{2k})^2}\Big)&=\frac{1}{2}\gamma+\frac{1}{2}\log\Big(\lim_{N\to\infty}\prod^{N}_{k=1}\frac{1+\frac{1}{k}}{(1+\frac{1}{2k})^2}\Big)\\&=\frac{1}{2}\gamma+\frac{1}{2}\log\Big(\lim_{N\to\infty}\prod^{N}_{k=1}\frac{k+1}{k}\frac{(2k)^2}{(2k+1)^2}\Big)\\ &=\frac{1}{2}\gamma+\frac{1}{2}\log\Big(\lim_{N\to\infty}\frac{\pi\Gamma(N+1)\Gamma(N+2)}{4\Gamma^2(N+3/2)}\Big)\\ &=\frac{1}{2}\gamma+\frac{1}{2}\log(\frac{\pi}{4}) \end{align} We have used the limiting value $$\lim_{N\to\infty}\frac{\Gamma(N+1)\Gamma(N+2)}{\Gamma^2(N+3/2)}=1$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.